IDENTIFYING THE SCHOOL COMMUNITY PREPAREDNESS RATE OF FLOOD DISASTER OF 34 PUBLIC JUNIOR HIGH SCHOOL BANDAR LAMPUNG - Listumbinang Halengkara (Journal Learning Geography, 2021)
This research aims to describe the school community preparedness in SMP Negeri 34 Bandar Lampung. The populationsin this quantitative descriptive research are the entire school community of SMP Negeri 34 Bandar Lampung; consist of school administrators, teachers, and students. The data were collected by using questionnaires ,observation, interview, and documentation. The preparedness Index Formula from LIPI is used for data analysis. The result indicates that the school community preparedness inS MP Negeri 34 Bandar Lampung was categorized as “prepared” with the index value 72,17, while school community components consist of school as institutions (S1) was categorized as “Prepared” with index value of 73,35, teacher (S2) was categorized as“prepared” with index value of 72,87, and student (S3) was categorized as “prepared” with index value of 65,75.Penelitian ini bertujuan untuk mendeskripsikan tingkat kesiapsiagaan komunitas sekolah di SMP Negeri 34 Bandar Lampung dalam menghadapi bencana banjir. Penelitian ini dilakukan dengan menggunakan metode deskripsi kuantitatif.  Populasi dalam penelitian ini adalah komunitas sekolah SMP Negeri 34 Bandar Lampung yang terdiri dari pengelola sekolah, guru, dan siswa. Pengumpulan data dilakukan dengan menggunakan kuisioner, observasi, wawancara, dan dokumentasi. Sedangkan teknik analisis data yang digunakan dalam penelitian ini adalah rumus Indeks Kesiapsiagaan Sekolah dari LIPI. Hasil penelitian ini menunjukan bahwa kesiapsiagaan komunitas sekolah SMP Negeri  34  Bandar Lampung  masuk ke dalam kategori siap dengan nilai indeks 72, 17,  sedangkan komponen komunitas sekolah terdiri dari sekolah sebagai lembaga (S1) masuk kedalam kategori siap dengan nilai indeks 73,35,  guru (S2) masuk ke dalam kategori siap dengan nilai indeks 72,87 dan siswa (S3) masuk ke dalam kategori siap dengan nilai indeks 65,75.